Perfil epidemiológico del parto cefalovaginal posterior a cesárea. Hospital Provincial General Docente Riobamba, 2015- 2020 - Allison Kimberly, Freire Fuentes (2020)
Introduction: Cephalovaginal delivery after a Cesarean surgery is a theme that was implemented in the guidelines of the Ministry of Health of Ecuador in 2016, through scientific evidence that expresses improving medical practice in the second level of care, it includes Cesarean deliveries, in which it is suggested to practice a posterior cephalovaginal delivery, providing integral care, if any obstetric complication occurs or needs surgical resolution, choose a referral to the third level of care. Objective To determine the epidemiological profile of cephalovaginal delivery after a Cesarean surgery. Materials and Methods: A retrospective cross-sectional descriptive study with data collection through the medical records of patients who have had a history of a previous Cesarean surgery and their last pregnancy ended in cephalovaginal delivery at the Riobamba Provincial General Hospital in a period 2015-2020. The rate of vaginal deliveries, Cesarean deliveries and percentage of vaginal deliveries in patients with a history of Cesarean surgeries were identified. Results: The study carried out at the Riobamba Provincial General Hospital entitled “Epidemiological profile of cephalovaginal delivery after a Cesarean surgery. Riobamba Provincial General Hospital, 2015-2020 “there is a prevalence of 32.99% of cephalovaginal deliveries after a Cesarean surgery. A comparison was made with the study carried out at the “Alfredo Paulson Women’s Hospital” entitled “Vaginal delivery with a history of a previous Cesarean surgery in the period from October 2016 to March 2017 at the “Alfredo Paulson Women’s Hospital” in which it states that 3% of deliveries attended were after a Cesarean surgery, another study carried out in the Pontificia Universidad Católica del Ecuador with the title “Associated factors with the success or failure of cephalovaginal delivery after a Cesarean surgery, at the Nueva Aurora Luz Elena Arismendi Gynecological-Obstetric Hospital, during the period June 2016 - June 2017” is 60.74%. Conclusions: The prevalence of cephalovaginal deliveries after a Cesarean surgery at the Riobamba Provincial General Hospital in the 2015-2020 period was 32.99% of post-Cesarean deliveries attended in the established time.